The welfare enhancing effects of a selfish government in the presence of uninsurable, idiosyncratic risk - R. Anton Braun; Harald Uhlig (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
This paper poses the following question: Is it possible to improve welfare by increasing taxes and throwing away the revenues? This paper demonstrates that the answer to this question is yes. We show that there may be welfare gains from taxing capital income even when the additional capital income tax revenues are wasted or consumed by a selfish government. Previous literature has assumed that government expenditures are exogenous or productive, or allowed for redistribution of tax revenue either via lump-sum transfers, unemployment compensation or other redistributive schemes. In our model a selfish government taxes capital above a given threshold and then consumes the proceeds. This raises the before-tax real return on capital and and thereby enhances the ability of agents to self-insure when they are long-term unemployed and have low savings. Since all agents have positive probability of finding themselves in that state there are cases where all agents prefer a selfish government to no government at all.
Keywords: 330